Science, democracy and emerging threats to scientific progress. - Feller, S (2012)
Can trustworthy science flourish in countries suffering from dictatorship? This is an increasingly relevant question. Many commercial publishers want to maximise their profits (as is to be expected in a capitalistic system) and are pushing into non-democratic countries with rapid economic growth like China. But how much can we trust the papers coming from countries with dictatorial regimes?